Customer Service and Customer Retention in Ghana’s Banking Sector: The Case of SG SSB Bank (Societe Generale, Ghana) - Dzogbenuku, Robert K.; Ahiabor, Godson K.; Amoako, George K. (Indian Journal of Marketing, 2014)
This paper assesses the extent to which SG-SSB Bank Limited satisfies its customers in order to retain them and to identify the effects of customer service retention on the bank’s fortunes. Regarding methodology of the study, a descriptive approach was considered using systematic random sampling method. The field instrument touched attributes of service performance, customer complaints, and service quality from 120 respondents. Multiple-linear regression model was used to determine the relationship between customer service delivery and customer retention. The study revealed that respondents were satisfied with service performance of quality service provided by the bank, but were dissatisfied with how the bank deals with customer complaints. It was concluded that though Ghana’s banking sector is growing, much needs to be done in terms of client service management and strengthening employees’ relationship with the management for growth. It is recommended that banks in Ghana must strive to meet ever increasing demands of clients if they want to remain relevant and competitive in the banking industry. The implication is that retaining customers through efficient customer service practices should be of prime focus of the top management for tangible results at the frontline. This will enhance corporate image in the banking sector, which is currently described as very competitive. Findings will be useful for policy development for sustainable growth in Ghana’s financial services sector and other financial markets in Africa.